2004
DOI: 10.1007/bf02894271
|View full text |Cite
|
Sign up to set email alerts
|

Serum adenosine deaminase, 5′ nucleotidase and malondialdehyde in acute infective hepatitis

Abstract: Serum adenosine deaminase (ADA), 5'nucleotidase (5'NT) and malondialdehyde (MDA) were estimated in patients with acute infective hepatitis (AIH) along with the routine parameters of liver disease.Present study is done to evaluate these special parameters in patients with clinical history of AIH and to assess the utility of these parameters as diagnostic/ prognostic indices of liver function and to correlate special parameters with routine liver function tests (LFT). ADA, 5'NT and MDA along with routine LFT was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 7 publications
5
20
0
Order By: Relevance
“…Increased plasma bilirubin level in PEMF-exposed group could also be a compensatory/retaliatory phenomenon in response to cellular peroxidative changes. This is because bilirubin functions as a powerful antioxidant, anti-mutagen, and an endogenous tissue protector in vivo [23]. Thus, there is a positive correlation between MDA content and plasma bilirubin level, which supports the study findings of Pratibha et al [23].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Increased plasma bilirubin level in PEMF-exposed group could also be a compensatory/retaliatory phenomenon in response to cellular peroxidative changes. This is because bilirubin functions as a powerful antioxidant, anti-mutagen, and an endogenous tissue protector in vivo [23]. Thus, there is a positive correlation between MDA content and plasma bilirubin level, which supports the study findings of Pratibha et al [23].…”
Section: Discussionsupporting
confidence: 81%
“…This is because bilirubin functions as a powerful antioxidant, anti-mutagen, and an endogenous tissue protector in vivo [23]. Thus, there is a positive correlation between MDA content and plasma bilirubin level, which supports the study findings of Pratibha et al [23]. On the contrary, another group of authors did not observe any significant modification in plasma bilirubin level in rats under the effect of long-term PEMF.…”
Section: Discussionsupporting
confidence: 71%
“…Significantly elevated adenosine deaminase activity was reported in cerebral cortex, cerebellum and brain stem of rats due to acute ethanol toxicity [41]. Pradipha et al [39] reported elevated MDA and ADA levels in acute infective hepatitis and also showed that lipid peroxidation is associated with loss of membrane integrity which subsequently causes the release of membrane-bound enzymes including ADA and 5' nucleotidase. In our study, we found elevated ADA activities in synaptosomal fractions of rat forebrains exposed to chronic ethanol administration.…”
Section: Resultsmentioning
confidence: 97%
“…It's an important enzyme for purine metabolism, converting nucleosides adenosine and 2'-deoxyadenosine into inosine and 2'-deoxyinosine, respectively [38]. ADA is considered as a membrane-bound enzyme [39]. Elevated activities of 5'-nucleotidase and adenosine deaminase were reported in rat myocardium exposed to ethanol without any significant change in the activities of gammaglutamyl transpeptidase and AMP deaminase [40].…”
Section: Resultsmentioning
confidence: 99%
“…All these processes culminate in an increase in serum MDA level. Hence increase serum MDA could be used as a marker for free radical mediated destruction of liver parenchymal cells [45]. Thus chronic exposure of lead in battery manufacturing workers of Western Maharashtra (India) clearly showed an adverse effect on heme biosynthesis and decrease activities of SOD and catalase in associated with increased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%